ANALISIS FAKTOR PENENTU ADOPSI PENGELOLAAN TANAMAN TERPADU PADI SAWAH MENGGUNAKAN PARTIAL LEAST SQUARE - Arya, Nyoman Ngurah; Mahaputra, I Ketut (Informatika Pertanian, 2020)
Efforts to promote integrated crop management of paddy have been carried out by farmer’s community in Bali through ICM-FFS in 2010 - 2013. This study aims to analyze the factors that influence the adoption of ICM technology of lowland paddy in Bali. The study was conducted in July - October 2017 in Tabanan, Gianyar, and Buleleng Regencies by a survey method. The number of respondents were 120 farmers. Data was analyzed by the Structural Equation Model-Partial Least Square (SEM-PLS). The results showed: (1) ) the characteristics of farmers, availability of labor, the presence of input shop, the characteristics of innovation / technology, the role of subak, the role of Government institutions, and the price of grain received by farmers are the factors that determine the adoption of the ICM technology of lowland paddy in Bali; (2) Structural Equation Model-Partial Least Square (SEM-PLS) is relevant and can be used to analyze the factors that determine the adoption of paddy ICM technology. The SEM-PLS method can be used an alternative method for analyzing the factors that influence the adoption of an innovation / technology in agriculture